Preparation and characterization of ZnO/ZnAl2O4-mixed metal oxides for dye-sensitized photodetector using Zn/Al-layered double hydroxide as precursor - Salih, Ethar Yahya; Sabri, Mohd Faizul Mohd; Tan, Sin Tee; Sulaiman, Khaulah; Hussein, Mohd Zobir; Said, Suhana Mohd; Yap, Chi Chin (Springer Verlag, 2019)
In this article, a simple new technique has been developed for the preparation of ZnO/ZnAl2O4-mixed metal oxide (MMO) as anode materials for visible light dye-sensitized (DS) photodetector using Zn/Al-layered double hydroxide (LDH) as precursor. Subsequently, a detailed correlation between the structural properties of the prepared samples and the photo-responsive behavior of the fabricated DS photodetectors was elucidated. Specifically, it is evidenced that a high surface area of the prepared mesoporous MMO anode materials exhibit excellent dye absorptivity and thus facilitate free electron transfer and increase the photocurrent in the fabricated DS photodetector. A significant bathochromic shift was observed in the optical energy of the prepared MMO samples under the increment of molar ratio, providing a short electron transfer pathway in the optimized Z7A DS photodetector, which in turn demonstrated photo-responsivity and photo-detectivity of 6 mA/W and 1.7 × 10+10 Jones, respectively. This work presents an alternative approach for the design of an eco-friendly MMO-based DS photodetector. [Figure not available: see fulltext.]. © 2019, Springer Nature B.V.